Implementation of first episode psychosis intervention in India - A case study in a low-and middle-income country - Sridhar Vaitheswaran; Graeme Currie; Vijaya Raghavan Dhandapani; Greeshma Mohan; Thara Rangaswamy; Swaran Preet Singh (Elsevier, 2021)
First Episode Psychosis (FEP) is a serious mental illness affecting adolescents and young persons. While many effective interventions are available, there has not been much research to understand the implementation of such interventions in India and other low- and middle-income countries (LMIC). We studied the implementation of an FEP intervention program in a specialist mental health facility in Chennai, India, using a well-established framework for doing so, the Consolidated Framework for Implementation Research (CFIR). We conducted 27 in-depth interviews with the service users (15 persons with FEP and 12 family caregivers of persons with FEP). We also conducted a focus group discussion with 8 service providers and in-depth interviews with 7 other service providers including those in the service management. A thematic analysis approach was used to identify emerging themes. First, we found CFIR effectively accommodated implementation challenges evident in LMICs; that is, it is transferable to LMIC settings. Second, we highlight barriers to implementation that include cost, limited human resources, cultural and professional hierarchy, divergence from evidence-based guidelines, and lack of awareness and stigma in the wider community. Third, we highlight facilitators for implementation such as, leadership engagement, the need for change that was recognized within the service, cosmopolitan perspectives derived from clinicians' local and international collaborative experiences and expertise, compatibility of the intervention with the existing systems within the organization, accommodating the needs of the service users, and rapport developed by the service with the service users. Fourth, we propose a model of service delivery incorporating a task-sharing approach for first episode psychosis in resource restricted settings based on the feedback from the stakeholders.